Motor Dysfunction Correlates with Frontal White Matter Ischemic Changes in Patients with Leukoaraiosis - Miguel Viana-Baptista; Paulo Bugalho; Constança Jordão; Olga Ribeiro; José António Esperança-Pina; José Ferro (Journal of Aging Research)
Objectives. To test the relation between white matter lesions (WML) location and physical performance, in aged patients. Methods. Subjects: 29 patients (17 males), aged >65 (mean age 72.6±5.2), with leukoaraiosis. WML was quantified with a visual scale; Apparent Diffusion Coefficient (ADC) was measured bilaterally in frontal periventricular lesioned white matter and frontal and parieto-occipital normal appearing white matter (NAWM). Motor performance was studied using the Short Physical Performance Battery (SPPB), single leg stand time, finger tapping and grooved pegboard tests (GPT). Results. There were significant correlations between the frontal region visual scale scores and SPPB chair stands (r=-0.379; P=.039) and Grooved Pegboard (r=0.393; P=.032); frontal NAWM ADC values and SPPB standing balance (r=-0.450; P=.014) and SPPB 4 meter walk (r=-0.379; P=.043). Conclusion. Frontal WML are negatively related to motor performance in patients with leukoaraiosis. DWI results suggest that this may be true even for NAWM.